Coping with cancer by young adults vs. importance of support from the nursing team - Cepuch, Grażyna; Bereś, Sylwia (Psychoonkologia, 2016)
Introduction: The difficult situation leads patients with cancer to choose from a variety of coping strategies and means that they need a special support. A support network is not only family, but also a bunch of professionals who accompany patients in the therapeutic process. Aim of the study : Evaluate the support received from the nursing team in the opinion of patients with cancer and the evaluation of these patients adapt to the disease through the selection of coping strategies. Material and methods : The study included 53 people of both sexes diagnosed with cancer (ages: 18 to 35 years old). In the study used: the scale Mini-MAC, Berlin Social Support Scale, and a epidemiological questionnaire. Results and conclusions : The most common strategy of choice among the group was a fighting spirit (M = 23.2). Style constructive coping style was the most popular choice (M = 44.6). Among women, the average values for perceived support available and actually obtaining support were slightly lower than in men, and in the case subscale of the need for support and seeking support were higher than those of the opposite sex. Statistical analysis revealed the existence of differences in strategy a positive revaluation (p = 0.0435) in relation to older subpopulation. In patients with cancer lasted more than a year most compounds with disease duration subscales had a pair of BSSS and a strategy of constructive style in scale Mini-MAC. The support provided by a nursing team can be considered as one of the important factors determining the choice of coping strategies of patients with cancer.